Development of Orchestration Course to Enhance Music Creative for Piano Major Student - Jiang, Xiaoning; Phokha, Pramote; Chiangthong, Nut (Journal of Ecohumanism, 2025)
This develops the orchestration course for piano major students and evaluates the orchestration course for piano major students. This study combines the principles of quasi-experimental and survey methods. Samples are 20 students majoring in piano at the School of Music Education of Xinghai Conservatory of Music. Research instruments are pretest and posttest, questionnaire, and interview. Data were analyzed by statistics and content analysis. The findings revealed that the orchestration course for piano major students consists of Music Composition Theory Foundation (α=0.9333), Instrument combination and part arrangement (α=0.898), Harmony processing and form structure (α=0.857), and Dynamics and effect processing (α=0.871), all of which are greater than 0.8, indicating that the pretest data has high reliability and the reliability of the research data is excellent and can be used for further analysis. The orchestration courses improve students’ comprehensive musical abilities and promote their all-round development in many aspects. However, there are also some problems in the course, such as insufficient resources, limited technical support, and insufficient cooperation opportunities, which must be addressed and improved. In order to solve these problems and further optimize orchestration courses, it is recommended that musical instrument and orchestration resources be increased and more robust technical support provided. By continuously combining students’ feedback to improve orchestration courses, we can better meet students’ needs and enhance teaching effects and learning experiences. Such efforts will help elevate students’ learning experience to a new level and achieve better teaching outcomes